Half a king - Abercrombie, Joe (New York : Del Rey, 2014)
Heir to the throne Yarvi, prompted by the murder of his father, embarks on a kingdom-transforming journey to regain the throne, even though having only one good hand means he cannot wield a weapon.
Map on lining papers.
"Published in hardcover in the United Kingdom by Harper Voyager"--Title page verso.
Keywords: Boys -- Fiction; Betrayal -- Fiction; Murder -- Fiction; Revenge -- Fiction; People with disabilities -- Fiction; Kings and rulers -- Succession -- Fiction; Fantasy fiction